The importance of physical linkage and connectivity to integrate the kampung and formal parts of the city - Claudia Montenegro Vieira Santos; Yohanes Basuki Dwisusanto; Yohanes Karyadi Kusliansjah (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
This research investigates the critical role of physical linkage and connectivity in the integration between formal and informal urban areas of the city, as well as recognizes aspects related to physical and social segregation that prevent this integration process. The objective is to understand this role in relation to the viability of integration. Qualitative method describes effectiveness of connectivity and linkage thorough the complexity of interaction between formal and informal areas in the built-form and open space. This research includes two important areas in Bandung, Indonesia, namely, Hegarmanah and Ciumbuleuit. Findings show Hegarmanah as an enclosed configuration with more incidence of controlled areas, through physical barriers, legal restrictions and circulation limitations. Ciumbuleuit presents less controlled areas, encouraging a wider use of public space, a variety of services, commerce, commuting. Interaction between pedestrians and built environment has experienced more adaptation, in a more open configuration. In conclusion, space configuration, borders, limited access and forms of control represent obstructions to the integration process, impairing physical connectivity, encouraging spatial segregation due to isolation and linkage disruption. Integration will be stimulated when space is articulated and able to adapt. Coexistence of seemingly social and physically segregated formal and informal parts of the city can be comprehended when there is a correct interpretation of the role of physical linkage and connectivity through the analysis of space.